2022
DOI: 10.34197/ats-scholar.2021-0083ps
|View full text |Cite
|
Sign up to set email alerts
|

Medical Students and the Drive for a Single Right Answer: Teaching Complexity and Uncertainty

Abstract: The arrival of Generation Z, the next generation of medical learners, has been accompanied by efforts to adapt teaching practices for this new group of students. Many have identified challenges associated with addressing the needs of modern medical learners. One particular trend we have observed is that medical students are increasingly requesting an “answer key” for all aspects of their medical education. Students often expect to have the correct answers readily available to them to ensure they have reached t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 48 publications
0
4
0
2
Order By: Relevance
“…Where possible, consensus was reached, but when differences of opinion persisted, the team agreed that acceptance was needed to move the project forward. Acceptance of a decision is not necessarily consensus; however, as Beatty (2006) unalterable facts and definitive answers (Patel et al, 2022;Scott et al, 2020), and therefore, an essential frameshift in their evolution from students to scientists is the ability to come to terms with this uncertainty (Bradley et al, 2021;Rosenberg et al, 2022;Witt et al, 2022). Our exposure to such diverse opinions in our own discussions will facilitate the development of learning activities that support students in their own transition.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Where possible, consensus was reached, but when differences of opinion persisted, the team agreed that acceptance was needed to move the project forward. Acceptance of a decision is not necessarily consensus; however, as Beatty (2006) unalterable facts and definitive answers (Patel et al, 2022;Scott et al, 2020), and therefore, an essential frameshift in their evolution from students to scientists is the ability to come to terms with this uncertainty (Bradley et al, 2021;Rosenberg et al, 2022;Witt et al, 2022). Our exposure to such diverse opinions in our own discussions will facilitate the development of learning activities that support students in their own transition.…”
Section: Discussionmentioning
confidence: 99%
“…Such disagreements, which are often informed by experiences with the misconceptions of varied cohorts of students, provide an excellent opportunity to address the uncertainty in the current body of knowledge. Students, particularly in science and medicine, often want clear unalterable facts and definitive answers (Patel et al, 2022; Scott et al, 2020), and therefore, an essential frameshift in their evolution from students to scientists is the ability to come to terms with this uncertainty (Bradley et al, 2021; Rosenberg et al, 2022; Witt et al, 2022). Our exposure to such diverse opinions in our own discussions will facilitate the development of learning activities that support students in their own transition.…”
Section: Discussionmentioning
confidence: 99%
“…In a study of college seniors, 58% indicated that they frequently seek feedback on their academic work, and another 38% indicated that they do so occasionally. 50 This has been attributed to various causes, including a desire for immediate gratification, 3,5,9 challenges in filtering and prioritizing large volumes of accessible information, 3,51 and a pragmatic awareness of the economic stakes of failure. 49,50 Satisfaction with the educational experience improves when Generation Z learners know what is expected of them.…”
Section: Immediate and Actionable Feedbackmentioning
confidence: 99%
“…Educators can also help learners engage with uncertainty in a meaningful way by acknowledging challenges that arise when contending with uncertainty. This can be done by making grappling with ambiguity a discrete learning objective in itself ( 15 ). Nonlinear learning and entrustment-based discussions have also been proposed to facilitate the same ( 10 , 12 ).…”
Section: When Several Roads Lead To Romementioning
confidence: 99%